Comparative performance of the objective vs. consensual seasonal climate forecasting approaches in West Africa and the Sahel - Tanimoune, Laouali I; Nimon, Pouwereou; Ali, Abdou; Houngnibo, Mandela C M; Alhassane, Agali; Mohamed, Hamatan; Soumana, Djibo; Assoumana, Boubacar Toukal; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2025)
AGRHYMET RCC-AOS, through the AICCRA project, has developed objective seasonal forecasting systems, combining advanced statistics, dynamical models, and artificial intelligence algorithms improving accuracy and reliability of climate forecasts across the region. Forecast accuracy assessment of the new objective seasonal forecasting approach and the existing consensual approach showed that the new objective seasonal forecasting approach significantly outperforms the consensual approach, achieving an average accuracy of 66% vs. 46% for the consensual approach. The highest skill is observed in predicting above-normal rainfall (94% vs 71% for the consensual approach) confirming the robustness of the objective system in identifying regions prone to flooding and heavy rainfall events. Similarly, performance for below-normal conditions (53% vs 21% for the consensual approach) demonstrates a good capacity to detect potential dry spells and drought risks. As the objective seasonal forecasting approach has been officially endorsed by the directors of NMHSs of the 17 countries in West Africa and the Sahel, transitioning from traditional consensual seasonal forecasts, this new approach will be used during the future Regional Climate Outlook Forums (RCOFs) in the region. There is a need to continue improving the WASS2S tool for a more holistic forecasting and strengthening the capacities of more NMHSs staff to ensure the sustainability and regional ownership of objective forecasts.